1996
DOI: 10.1016/0885-3924(95)00161-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nausea in advanced cancer patients: A retrospective assessment of a metoclopramide-based antiemetic regimen

Abstract: The purpose of this retrospective study is to assess the frequency and intensity of chronic nausea in patients admitted to the Palliative Care Unit and the results of a metoclopramide-based treatment regimen. We reviewed the medical records of 100 consecutive patients admitted to the Palliative Care Unit at the Edmonton General Hospital until death during 1992-1993. All patients had terminal cancer and normal cognitive function. All patients completed the Functional Analogue Scale for appetite, nausea, pain, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 13 publications
2
40
0
2
Order By: Relevance
“…Accepting the value of 3 in a 0-10 visual analogue scale as the threshold for mild to moderate intensity [20], most of the patients referred to the SCC clinic had low-intensity nausea and shortness of breath. These findings have been reported in similar groups before [10,21].…”
Section: Discussionsupporting
confidence: 78%
“…Accepting the value of 3 in a 0-10 visual analogue scale as the threshold for mild to moderate intensity [20], most of the patients referred to the SCC clinic had low-intensity nausea and shortness of breath. These findings have been reported in similar groups before [10,21].…”
Section: Discussionsupporting
confidence: 78%
“…However, dosages of 1 mg/kg have been safely used among poisoned patients and oncology patients. 5,35 Our study was too small to assess effects of various dosages of metoclopramide. Future research should assess larger doses of metoclopramide among emergency department patients with migraines.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies were identified in a systematic review from this department to determine the effectiveness of metoclopramide in relieving N/V in patients with advanced cancer (unpublished data). Three studies [11][12][13] were of randomised crossover design, three were case reports [14][15][16] and one [17] a retrospective case note review. There was a statistically significant improvement in nausea in three studies and of vomiting in two series, but the studies vary in quality and methodology, and the numbers of patients included is small.…”
Section: Discussionmentioning
confidence: 99%